Spontaneous pneumothorax during pregnancy in a patient with kyphoscoliosis: An uncommon occurrence - a case report (Indian Journal of Case Reports, 2026)
Spontaneous pneumothorax is extremely uncommon during pregnancy. It is not a common complication of kyphoscoliosis, either. For the treatment of the entity, there are no universal guidelines. We report the case of a 30-year-old second gravida in her second trimester of pregnancy with spontaneous pneumothorax. She was managed with emergency tube thoracostomy and other supportive treatment. When pregnant women experience dyspnea and chest pain, the differential diagnosis of pneumothorax should be taken into account. With successful treatment, adverse outcomes are rare.